A reading of the jurisprudential and fundamentalist views of Abu al-Qasim Abd al-Rahmane bin Muharz al-Qayrawani (d. 450 AH) - Maidi , abderrahmane (Journal of Social Sciences and Humanities, 2021)
This research presents an overall reading of some of the jurisprudential and fundamentalist views of Imam Abu al-Qasim Abd al-Rahman ibn Muhariz al-Qayrawani, by translating and introducing him, in his name, drawing, and mentioning his homeland and his journey, as well as getting to know his disciples and Sheikhs, and mentioning a number of sayings of what was said in his biography; and trying to monitor a number of Opinions and quotes about him in the books that were concerned with the Code in particular, including the book ((Alerts deduced on the written and mixed books)) by Judge Ayad bin Musa bin Ayad bin Imron (died: 544 AH), where he did not leave to refer to Imam bin Mahraz, may God have mercy on him in the folds of his book , Which is between approval, violation, correction, and delinquency He rebukes the blog, because he has a book in explaining the blog, and it is one of the heritage that the days lost and did not reach us. There are opinions, whether they are in agreement with the majority of the Maliki people or the famous in the doctrine, or they are contrary to that, and the extent if they are considered within the participatory work and the doctrinal investigation that is defined in the characteristics of the Moroccan Maliki school, where correcting narrations and headphones and showing evidence and indications, and other things that are defined in the curricula of applicants From the Maliki masters, the study is presented according to what suits the maqam, a reading in a group of issues in which an opinion about the imam was narrated, and a reading of those opinions within the context in which it was presented, with the goal of introducing this underwhelmed scientist, which the researchers did not reach to introduce him and his jurisprudence. We present an analytical reading of the available translations from which we mention his name, his homeland, his journey, his elders, his students, and the conclusion of his death, may God have mercy on him.